KEPEMIMPINAN PEREMPUAN DI RANAH PUBLIK DALAM KAJIAN PERSPEKTIF FIQIH - Henderi Kusmidi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: The existence of women in the context of strategic leadership in various lines of life including in government becomes a controversial issue among classical and contemporary scholars. Some scholars tend to allow women to be leaders in strategic positions, while some other scholars tend not to allow women to be leaders. Their views on whether or not women can become leaders are supported by each of the arguments they build. However, if each of the arguments they build is analyzed comprehensively, then it seems that the more logical and rational views of the scholars who tend to allow women to become leaders with consideration of the benefits and interpretations that will result. The implications of this are creative, innovative, constructive and gender equality perspectives in the context of leadership in all walks of life of people, nations and countries in the current era of globalization, reform and advancement of information technology. Women's leadership becomes a public issue that is always hotly discussed, even provoking polemics and debates between the pros and cons of women's leadership in the State or other public spheres. Despite the recognition of basic human rights including the right of women to be equal with men, it seems to have experienced a significant increase in various parts of the world. In terms of leadership, the position of women is still faced with the position of men. Women are considered not fit to occupy positions related to power that are considered appropriate only for men. finally to the kitchen is also often used as a tool to justify acts of injustice against women.Keywords: Leadership, Womans, Public Area dan Islamic Law;